Adaptive changes in young football players working in a modified tactical periodization model based on the example of endurance - Marta SZYMANEK-PILARCZYK; Michał NOWAK; Jacek WĄSIK (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2024)
Introduction: Adequate endurance is a critical element of success in football, both at professional and amateur levels. Therefore, this study aimed to assess the effectiveness of training based on a modified wave (repeating) periodization model on the endurance of players aged 12-16 at the RKS Raków Academy in 2018-2022. Material and Method: The analysis involved football players aged 12 to 16 with 4-8 years of training experience, involved in a program called "wave periodization". Two tests were performed each year, one in June (Test A) and the other one in December (Test B). Maximal Aerobic Speed (MAS) and Velocity Intermittent Fitness Test (VIFT) indicators were measured using the Intermittent Fitness Test 30-15 by M. Buchheit. Results: Tests conducted after a 6-month training cycle in subsequent years statistically significantly increased the MAS (Z = 14.45; p < 0.001) and VIFT (Z = 13.11; p < 0.001) values. The importance of MAS (F = 206.31; p < 0.001) and VIFT (F = 209.11; p < 0.001) increased in both tests in subsequent years of training. The player's position on the pitch does not correlate with the results of endurance tests. However, there is a relationship between players' age and endurance. Conclusions: The training based on the wave periodization model significantly increased the endurance of the RKS Raków Częstochowa Academy players. The research shows that in each year between 2018 and 2022, the training intervention increased the tested players' MAS and VIFT values. The tested players' position on the pitch does not correlate with the results of endurance tests. The recorded positive correlation between age and endurance confirms the current knowledge.